The Construal of Midwives by Pregnant Women with a Body Mass Index Greater Than or Equal to 30 kg/m2 (BMI ≥ 30 kg/m2): A Repertory Grid Study. (3rd March 2016) - Hodgkinson, Emma L; Smith, Debbie M; Hare, Dougal Julian; Wittkowski, Anja
Abstract : Objective: To explore the construal of midwives by pregnant women with a body mass index greater than 30 kg/m 2 (BMI ≥ 30 kg/m 2 ). Method: Ten pregnant women with a BMI ≥ 30 kg/m 2 were recruited from antenatal clinics at a maternity hospital in the North West of England. Each participant completed a repertory grid. The participants chose people to match roles including themselves, pregnant women, midwives of different BMIs and hypothetical elements. They also generated psychological constructs to describe them. Results: Pregnant women with a BMI ≥ 30 kg/m 2 construed themselves as vulnerable and self‐conscious. Some women endorsed obesity‐related stereotypes for themselves and felt responsible for their weight. The midwife with a BMI 18 < 30 kg/m 2 was considered to be most similar to the ideal midwife, while the midwife with a BMI ≤ 18 kg/m 2 was construed as having an undesirable interpersonal style. The midwife with a BMI ≥ 40 kg/m 2 was often construed as sharing similar experiences to the pregnant women with a BMI ≥ 30 kg/m 2, such as struggling with the psychological consequences of a raised BMI. Some women construed the midwife with a BMI 30 < 40 kg/m 2 in a positive way, whereas others viewed it as sharing similar feelings about weight as the midwife with a BMI ≥ 40 kg/m 2 . Conclusions: The pregnant women with a BMI ≥ 30 kg/m 2 in this study described perceptions of themselves and the midwives responsible for their care, which may affect their engagement and satisfaction with services. Pregnant women with a BMI ≥ 30 kg/m 2 should be involved in service development activities to ensure the structure of services and the language used by midwives are acceptable and do not confirm weight‐related stereotypes. Copyright © 2016 John Wiley & Sons, Ltd. Key Practitioner Message: Pregnant women with a BMI ≥ 30 kg/m 2 construe themselves as vulnerable and self‐conscious and perceive themselves responsible for their weight. Pregnant women with a BMI ≥ 30 kg/m 2 construe midwives with a low BMI as having an undesirable, cold, interpersonal style. Midwives with a raised BMI are construed as similar to the women, because they share the uncomfortable psychological consequences of a raised BMI. The nature of pregnant women's construal may affect their engagement and satisfaction with maternity services and midwifery care.